2021
DOI: 10.23876/j.krcp.21.015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal microRNA profiling in type 2 diabetes patients taking dipeptidyl peptidase-4 inhibitor compared with sulfonylurea

Abstract: Background: Dipeptidyl peptidase-4 (DPP-4) inhibitor has been reported to have kidney-protective benefits. To elucidate how antidiabetic agents prevent diabetic kidney disease progression, it is important to investigate their effect on the kidney environment in type 2 diabetes mellitus (DM) patients. Herein, we investigated the expression pattern of urinary exosome-derived microRNA (miRNA) in patients taking a combination of DPP-4 inhibitor and metformin (DPP-4 inhibitor group) and compared them with patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Interestingly, the literature has demonstrated a role for exosomes in physiological and pathological conditions, such as in the progression of cancer, which has been vastly described in the literature [ 17 , 18 , 19 , 20 ]. In addition, circulating and urinary exosomes are being used to identify key proteins and microRNA (miRNAs), circular RNAs (circRNA), or long non-coding RNA (lncRNA) associated with different diseases including type 2 diabetes, nephropathy, aldosteronism, atherosclerosis, and several types of cancer (bladder, gastric, prostate cancers) [ 21 , 22 , 23 , 24 , 25 ]. Therefore, it seems that the exosomes carry potential molecules to help in the diagnosis of diseases.…”
Section: Exosomesmentioning
confidence: 99%
“…Interestingly, the literature has demonstrated a role for exosomes in physiological and pathological conditions, such as in the progression of cancer, which has been vastly described in the literature [ 17 , 18 , 19 , 20 ]. In addition, circulating and urinary exosomes are being used to identify key proteins and microRNA (miRNAs), circular RNAs (circRNA), or long non-coding RNA (lncRNA) associated with different diseases including type 2 diabetes, nephropathy, aldosteronism, atherosclerosis, and several types of cancer (bladder, gastric, prostate cancers) [ 21 , 22 , 23 , 24 , 25 ]. Therefore, it seems that the exosomes carry potential molecules to help in the diagnosis of diseases.…”
Section: Exosomesmentioning
confidence: 99%
“…T2D urine miRNA studies mainly studied T2D patients with kidney complications [ 178 , 179 , 180 , 181 , 182 , 183 , 184 ], except one study compared patients with different T2D treatments [ 185 ] ( Table 10 ). Most studies profiled miRNAs from urinary exosomes, while a few profiled urine supernatants [ 178 , 184 ].…”
Section: Epigenomics Biomarkers For T2dmentioning
confidence: 99%
“…Several studies have showed that have potential renoprotective effects through reducing inflammation, fibrosis, and oxidative damage (Tanaka et al, 2014;Daza-Arnedo et al, 2021). In addition, DPP4i have been shown to provide renoprotective benefits in TAC-induced kidney injury through urinary exosome-derived miRNA profiling and anti-apoptotic effects (Huang et al, 2012;Cho et al, 2021). However, it remains unclear whether these protective effects can be further enhanced by combining DPP4i with GTE.…”
Section: Introductionmentioning
confidence: 99%